Chronicling Stankonia the rise of the hip-hop South - Bradley, Regina N. (The University of North Carolina Press, 2021)
"Chronicling Stankonia situates hip hop as an intervention in constructing post-Civil Rights black identities and cultural discourse. For southern blacks, the past is often restricted to three recognizable historical moments - the Antebellum Era, Jim Crow, and the Civil Rights Movement. Aside from the deeply traumatic experience of these periods of history, they also serve as cornerstones of validating and recognizing southern blacks' experiences. However, the challenge for post-Civil Rights generations of southern blacks is speaking truth to power when their truths depart the trajectory of what was considered power in the past. Chronicling Stankonia updates the black South using hip hop as an agent to reflect multiple intersections of time, race, and southernness in the late twentieth and early twenty-first centuries. Part of southern hip hop culture's truth remains attached to the past but its power is grounded in the fact that younger southerners use hip hop to embrace the possibility of multiple Souths, multiple narratives, and multiple entry points into contemporary southern black identities"--
Includes bibliographical references and index
Keywords: OutKast -- Musikgruppe; Hip-Hop; Schwarze; Ethnische Identität; USA -- Südstaaten; Rap (Music) / Social aspects / Southern States; Rap (Music) / Southern States / History and criticism; Hip-hop / Southern States; African Americans / Race identity / Southern States; OutKast (Musical group); African Americans / Race identity; Hip-hop; Rap (Music); Rap (Music) / Social aspects; Southern States; Criticism, interpretation, etc